2013
DOI: 10.2105/ajph.2012.300829
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Community Social Norms on Spousal Violence: A Population-Based Multilevel Study of Nigerian Women

Abstract: Efforts to end violence against women, particularly spousal violence, should consider broader social and contextual determinants of violence including social norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 38 publications
5
81
0
1
Order By: Relevance
“…Individual-level sociodemographic variables were used as controls. Prior research shows that younger age (Bates et al, 2004;Rahman et al, 2011), early marriage (Erulkar, 2013), lower education (Erulkar, 2013;Linos et al, 2013), living in the poorest households (Rahman et al, 2011;Sambisa, Angeles, Lance, Naved, & Thornton, 2011), having many children (Sambisa et al, 2011), not having independent income (Naved & Persson, 2005), and living in rural areas (Yount & Li, 2009) are associated with elevated risks of IPV. In this study, age, age at first marriage, and age at first birth were all measured in years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual-level sociodemographic variables were used as controls. Prior research shows that younger age (Bates et al, 2004;Rahman et al, 2011), early marriage (Erulkar, 2013), lower education (Erulkar, 2013;Linos et al, 2013), living in the poorest households (Rahman et al, 2011;Sambisa, Angeles, Lance, Naved, & Thornton, 2011), having many children (Sambisa et al, 2011), not having independent income (Naved & Persson, 2005), and living in rural areas (Yount & Li, 2009) are associated with elevated risks of IPV. In this study, age, age at first marriage, and age at first birth were all measured in years.…”
Section: Methodsmentioning
confidence: 99%
“…For example, 41% women in Turkey, 40% in Zimbabwe, and 46% women in Cambodia agree with husbands' beating on account of minor violations of their socially determined responsibilities such as burning food, arguing with husbands, mismanaging money, neglecting children, or refusing sex (Marshall & Furr, 2010; United Nations Children's Fund [UNICEF], 2013). Although IPV victims are not responsible for their own victimization, attitudes justifying IPV may be associated with the likelihood of being victimized (Linos, Slopen, Subramanian, Berkman, & Kawachi, 2013;Okenwa, Lawoko, & Jansson, 2009;Waltermaurer, 2012). For example, in a multicountry study, Kishor and Johnson (2004) found that in each of the eight countries, women who agreed that husbands are justified to beat the wife in specific circumstances, were more likely to report ever experiencing violence.…”
mentioning
confidence: 99%
“…In addition to individual-level risk and protective factors, GBV is considered perpetuated by macrolevel forces including male entitlement or ownership of women, rigid gender roles, and acceptance of interpersonal violence at a social level [12], which can be reinforced by law and practice. Evidence supports the influence of contextual factors on GBV, for example, community-level tolerance of violence is associated with experiences of IPV [13]. At the national level, these dynamics may be codified in criminal and administrative law, for example, in laws establishing violence as a crime or ensuring or limiting women's property inheritance rights.…”
mentioning
confidence: 98%
“…In a Nigerian study, of the 18,798 ever-married women in the study, 19% reported exposure to sexual or physical violence from a spouse. The prevalence was geographically patterned by state and ranged from 3% to 50% (Linos, Slopen, Subramanian, Berkman, & Kawachi, 2013). Violence between the adult members of a family can have serious negative consequences for the unborn children of pregnant women (Sharps, Laughon, & Giangrande, 2007) or older children, who witness the violence (Krug et al, 2002;Orford et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of demographic and health surveys conducted in Sub-Saharan Africa showed that when use of violence was culturally more accepted, the rate of IPV against women was more frequent (Uthman, Lawoko, & Morad, 2010). A Nigerian study also found a connection between state-level permissive attitudes towards spousal violence and the rate of women's reports of physical and sexual violence by their husbands (Linos et al, 2013). The authors conclude that efforts to end violence against women, particularly spousal violence, should consider broader social and contextual determinants of violence, including social norms.…”
Section: Introductionmentioning
confidence: 99%